Serotonin, dieting, and bulimia nervosa. - Cowen, P; Smith, K (1999)
Dieting is a common behaviour which may trigger eating disorders such as bulimia nervosa in predisposed subjects. We found that in healthy women moderate dieting for 3 weeks lowered plasma concentrations of the 5-HT precursor, L-tryptophan (TRP) and impaired brain 5-HT neurotransmission as judged by 5-HT neuroendocrine tests. In recovered female subjects with a history of bulimia nervosa we found that TRP depletion produced by an amino acid mixture lacking TRP caused a temporary return of depressive symptoms together with concerns about weight and shape and fear of loss of control of eating. Taken together the data suggest that dieting-induced decreases in TRP availability may trigger the development of bulimia nervosa is susceptible individuals.